Job switching: What's in it for me? - Mikaela Backman; Maureen Kilkenny (European Regional Science Association (ERSA), 2014)
This paper analyse how previous experience and affiliation influence individual employees but also the current employers. Knowledge can be embodied in several different forms, in individuals, in books, in machines, or in processes. Human capital refers to embodied knowledge in individuals, comprising qualifications acquired through education, experience, skills acquired through learning by doing and training, inherited abilities, ethics, and habits. Individuals are in this setting knowledge carriers and since an individual cannot be separated from these characteristics the knowledge can therefore not be sold or used as collateral. The diffusion of human capital is thereby determined by the individual's mobility across locations and firms. Disembodied knowledge on the other hand arises because of knowledge spillovers and positive externalities. This paper focus on the diffusion of knowledge through the inter-firm, inter-region and inter-sectoral mobility. This has to the authors knowledge not been analysed this systematic before. Hence, this paper investigate the existence, much less the effects of "brain circulation", the mode of knowledge transfer between firms in regions and the benefits of regional workforce density and localization economies. The empirical design is based on employer-employee matched data covering most active firms and individuals in Sweden over the time period 1990 to 2010. The experience of each individual is identified by tracking the individual over the last ten years (from 2001). Experience is defined in abroad context where the scale and scope of previous establishments, firms, geographical locations and sectors are used. We test how these previous experiences benefit the individual in terms of higher wages but also how it influence the current employer. The effect on the employer is measured through the firms productivity, profitability and the ability to be innovative. By having this broad definition of experience we can decipher if it is the diversified experience in terms of number of establishments, firms, locations or the sectors that is beneficial for the individual respectively the firm. Hence, we can analyse if individuals that change employers, locations and even jump between different sectors benefit and if firms should focus on hiring individuals that have a large experience and what type of experience that is beneficial.
Keywords: D21; D22; D85; J24; J31; J62; 330; affiliation; network; diversified experience; employer-employee data